PENERAPAN MODEL PEMBELAJARAN OUTDOOR ACTIVITY DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI - Helder Nababan (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This type of research is a classroom action research with input variables namely students of class XI SMAN 1 Pahae Julu, North Tapanuli Regency, Geography subject teachers, facilities that support learning, and environmental conditions around the school. Based on the results of the study, the researchers concluded that the learning outcomes of Geography in class XI students of SMAN 1 Pahae Julu, North Tapanuli Regency could be improved through the use of Outdorr activity type cooperative learning models. This is evidenced from the student learning outcomes obtained by students completeness in the initial conditions of the number of 30 students, there are 7 people or 23.33% who are given the test to get the value of the complete criteria. In the first cycle there were 22 people or 73.33% who were given the test to get the complete criteria, and in the second cycle there were 27 students or 90.00% received the complete criteria. From the results of the study concluded that the application of Outdoor activity learning models in the subject of Geography can improve student learning outcomes in the material Analyzing Population Aspects in class XI SMA Negeri 1 Pahae Julu academic year 2018/2019 Keywords: Outdoor activity, demographic aspects Abstrak: Jenis penelitian ini adalah penelitian tindakan kelas (PTK) dengan variabel input yakni siswa kelas XI SMAN 1 Pahae Julu Kabupaten Tapanuli Utara, guru mata pelajaran Geografi, sarana yang mendukung pembelajaran, serta kondisi lingkungan sekitar sekolah. Berdasarkan hasil penelitian, peneliti menyimpulkan bahwa hasil belajar Geografi pada pada siswa kelas XI SMAN 1 Pahae Julu Kabupaten Tapanuli Utara dapat ditingkatkan melalui penggunaan model pembelajaran kooperatif tipe Outdorr activity. Hal ini dibuktikan dari hasil belajar siswa diperoleh ketuntasan siswa pada kondisi awal dari jumlah 30 orang siswa, terdapat 7 orang atau 23,33% yang diberikan tes memperoleh nilai kriteria tuntas. Pada siklus I terdapat 22 orang atau 73,33% yang diberikan tes memperoleh nilai kriteria tuntas, dan pada siklus II terdapat 27 orang siswa atau 90,00% memperoleh nilai kriteria tuntas. Dari hasil penelitian maka disimpulkan penerapan model pembelajaran Outdoor activity pada mata pelajaran Geografi dapat meningkatkan hasil belajar siswa pada materi Menganalisis Aspek Kependudukan di kelas XI SMA Negeri 1 Pahae Julu tahun pelajaran 2018/2019 Kata kunci: Outdoor activity, aspek kependudukan